2003
DOI: 10.1289/ehp.6254
|View full text |Cite
|
Sign up to set email alerts
|

Profile of urinary arsenic metabolites during pregnancy.

Abstract: Chronic exposure to inorganic arsenic (In-As) from drinking water is associated with different health effects, including skin, lung, bladder, and kidney cancer as well as vascular and possibly reproductive effects. In-As is metabolized through the process of methylation, resulting in the production and excretion of methylated species, mainly monomethylarsenate (MMA) and dimethylarsenate (DMA). Because a large percentage of the dose is excreted in urine, the distribution of urinary In-As, MMA, and DMA is consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 24 publications
5
61
1
2
Order By: Relevance
“…Similar results have been reported from experimental studies on mice, with most of the arsenic in foetal tissues being dimethylarsinate (Devesa et al, 2006). The metabolic methylation of arsenic via one-carbon metabolism increases in women during pregnancy (Concha et al, 1998;Hopenhayn et al, 2003a). For that reason, the human foetal is likely to be exposed to more inorganic arsenic and methylarsonate in early gestation.…”
Section: Distributionsupporting
confidence: 80%
“…Similar results have been reported from experimental studies on mice, with most of the arsenic in foetal tissues being dimethylarsinate (Devesa et al, 2006). The metabolic methylation of arsenic via one-carbon metabolism increases in women during pregnancy (Concha et al, 1998;Hopenhayn et al, 2003a). For that reason, the human foetal is likely to be exposed to more inorganic arsenic and methylarsonate in early gestation.…”
Section: Distributionsupporting
confidence: 80%
“…Total arsenic concentrations were unrelated to gestational week (r s = −0.03, P = 0.66). Although other studies found that arsenic methylation increased with gestational week (27,28), methylation efficiency measured as the ratios of MMA to iAS, and DMA to MMA, was not associated with gestational week in our sample (r s = −0.002, P = 0.98 and r s = 0.01, P = 0.86, respectively), possibly due to the narrow gestational window under observation (IQR 23.9-28.0 wk). Among the 180 subjects who reported using their tap water for drinking or cooking, home water arsenic concentration was associated with total urinary arsenic concentration (r s = 0.43, P < 0.0001).…”
Section: Resultsmentioning
confidence: 81%
“…The underreporting and misclassification of spontaneous abortion outcomes in this study could have led to an underestimation of the association between prenatal arsenic exposure and early pregnancy loss. Second, previous studies have shown that arsenic metabolism efficiency among pregnant women varies across trimesters, with evidence to suggest that metabolism efficiency increases in the first trimester (Gardner et al 2011; Hopenhayn et al 2003). However, it was not possible to evaluate the effect of trimester-specific arsenic exposure in this study.…”
Section: Discussionmentioning
confidence: 99%